Victor Turner’s Social Drama and T. S. Eliot’s Ritual Drama - Grimes, Ronald L. (Anthropologica, 2022)
This article "intertextualizes" a case study by Victor Turner with a play by T. S. Eliot, without arguing that either is derived from the other. The case study, published in 1974, brings Turner’s theory of social drama to bear on the confrontation between Archbishop Thomas Becket and King Henry II of England in 1170 A.D. The play is a ritual drama published by Eliot in 1935 for a commemoration of Becket’s martyrdom. Thus, the genres and intentions of the two works differ considerably. Nevertheless, reading each text in the light of the other leads to a discussion of the mutual critiques they imply, and reveals the dominant metaphors that organize Turner’s and Eliot’s treatment of the same historic event.